(untitled) - J Michael O'Malley (Cambridge, New York, 1990)
This book presents the view that language is a complex cognitive skill that can be described within the context of cognitive theory. A theory of second language acquisition, to be successfull, must be able to describe how knowledge about language is stored in memory and how the process of second language acquisition ultimately results in automatic language comprehension and production
Keywords: second language acquisition